Babaeng nanlaban a critical analysis on how violent female narratives in Philippine cinema counter gendered disinformation - Ansong, Ana Loraine Fabian; Arumpac, Adjani G. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This research proposes a critical analysis of the concept of the babaeng nanlaban (woman who fought) in Philippine Cinema. It also discusses the babaeng nanlaban narratives as countervoices against gendered disinformation and violence. Additionally, it seeks to challenge the concept of violence in cinema and redefine it as a retributive counterattack when associated with the character of the empowered female. The research primarily employs a Feminist Critical Discourse Analysis that allows for a critical examination and interpretation of the themes, visual languages and cues, and overall contextualization of the films as mediating tools for empowerment. The study focuses on a selection of films produced from 2016 to 2022, at the Digital Age of Philippine Cinema under the Duterte regime. This time period marked by authoritarian rule, gendered disinformation, and structural violence is key to determining the reimagined image of the empowered female. The research aims to put forward the stories of empowered women as told by actual empowered women filmmakers. It seeks to contribute to the fight against gendered disinformation by providing templates for the recalibration of both scholarship and media.

Keywords: babaeng nanlaban, Feminist Philippine Cinema, gendered disinformation, misogyny, Duterte regime
Ang pananaliksik na ito ay nagmumungkahi ng isang kritikal na pagsusuri ng konsepto ng babaeng nanlaban sa Pelikulang Pilipino. Tinatalakay din nito ang mga naratiho ng habaeng nanlaban bilang mga boses na sumasalungat sa gendered disinformation, isang paraan ng pagpapalaganap ng marahas na kasinungalingan ukol sa kababaihan. Sinisikap nitong hamunin ang konsepto ng dahas sa pelikula na kaugnay ng karakter rig babaeng makapangyarihan. Isinasagawa ito sa pamamagitan ng pagtukoy sa dahas bilang mapamarusang tugon na may layunin na pagkamit ng hustisya.

Sa pananaliksik, ginamit ang metodolohiya ng Feminist Critical Discourse Analysis na nagbibigay-daan sa kritikal na pagsusuri at pagpapakahulugan ng mga tema, wikang biswal, at pangkalahatang kontekstuwalisasyon ng mga pelikula bilang tagapagpamagitan ng kapangyarihan. Ang mga pelikulang sinuri ay gawa mula 2016 hanggang 2022, sa panahong nakatakda si Rodrigo Duterte bilang pangulo ng Republika ng Pilipinas. Batid sa kapanahunang ito ang awtoritaryan na pamamahala, gendered disinformation, at istruktural na karahasan. Dito mahalagang tukuyin ang panibagong imahe ng kapangyarihan ng kababaihan.

Layunin ng pananaliksik na ito na ilahad ang mga makapangyarihang kuwento ng mga kababaihan na isinasalaysay mismo ng mga kababaihan gamit ang pelikula. Layunin din nitong makiisa sa paglaban sa gendered disinformation sa pamamagitan ng pagbibigay ng gabay tungo sa positibong pagbabago ng literatura at medya.
Vita.
Thesis
Includes bibliographical references (pages 164-208) and appendices (pages 209-11).
Keywords: Women in mass media; Violence in motion pictures; Violence in women in popular culture -- Philippines